2020
DOI: 10.3390/ijerph17176319
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Soil PAHs and Health Risk Influenced by Coal Usage Processes in Taiyuan City, Northern China

Abstract: The quality of urban soil is closely related to the safety of public places and the guarantee of food quality. This study investigated the level, distribution, source, and carcinogenic risk of 16 U.S. EPA (Environmental Protection Agency) priority polycyclic aromatic hydrocarbons (PAHs) in urban, agricultural, and montane soil in Taiyuan. The ∑16PAHs level varied from 104.78 to 6594.63 ng g−1 with a mean of 922.93 ng g−1, and 47.73% of the soil samples were severely contaminated, with a concentration higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Li et al [ 42 ] showed that the spatial distribution of PAHs and B[ a ]P produced by industry impact the surrounding quality of soil. They pointed to following sources: combustion of coal (40.77%), exhausts from vehicles (32.94%), combustion of biomass (14.89%), and cooking (11.40%).…”
Section: Sources Of Human Exposure To B[ a ]Pmentioning
confidence: 99%
“…Li et al [ 42 ] showed that the spatial distribution of PAHs and B[ a ]P produced by industry impact the surrounding quality of soil. They pointed to following sources: combustion of coal (40.77%), exhausts from vehicles (32.94%), combustion of biomass (14.89%), and cooking (11.40%).…”
Section: Sources Of Human Exposure To B[ a ]Pmentioning
confidence: 99%
“…Taiyuan City, the capital of Shanxi Province, was selected as the research area in this study ( Figure 1 ). Taiyuan, as an important industrial base in northern China, has long been plagued by air pollution, especially PAH pollution, due to high energy consumption and poor air diffusivity [ 30 , 31 , 32 , 33 ]. According to statistics, the annual consumption of oil in Taiyuan was 1.9 million tons standard coal equivalent, and the annual coal consumption was 79.0 million tons of coal, accounting for 20.4% of the total oil consumption and 29.4% of the coal consumption in Shanxi Province, respectively [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Σ 7 CarPAHs contributed approximately 37.6% of the Σ 16 PAHs, with a mean of 188.0 ng/g (range 12.8-803.2 ng/g). A past study indicated that human activities are the main source of PAHs (Abdel-Shafy and Mansour, 2016; Li et al, 2020), and as shown in Figure 1B, the landform of Taiyuan city is a basin, with low elevations in the middle region and high elevations in the east and west. Human activities and heavy pollution enterprises are distributed mainly in the middle plain area at low elevations.…”
Section: Contamination Levelmentioning
confidence: 99%